Rapid Resolution of Cholangitic Abscess and Biliary Sepsis in a Liver Transplant Recipient after Hepatic Artery Revascularization. (1st June 2016) - Trakroo, Sushrut; Qureshi, Kamran
Abstract : Hepatic arterial flow is paramount in preserving biliary integrity. We present an interesting clinical scenario of a liver transplant recipient with biliary anastomotic stricture who developed biliary abscess and sepsis after Endoscopic Retrograde Cholangiopancreatography. The abscess did not respond to maximal medical management, percutaneous drainage, and adequate endoscopic biliary drainage. Clinically, patient continued to deteriorate and imaging identified hepatic artery stenosis which was treated with percutaneous intra-arterial stenting. Revascularization and perfusion of infected area led to rapid resolution of abscess and sepsis. This case emphasizes the anatomic basis of biliary ductal pathology. An important educational point is to understand that interrupted hepatic arterial supply can lead to biliary complications in liver transplant recipients and early correction of perfusion deficit should be pursued in such cases. In nonresolving hepatobiliary infections after liver transplantation, hepatic arterial compromise should be looked for and if present promptly treated. Reperfusion of biliary system in our patient led to improved antibiotics penetration, resolution of abscess and sepsis, and healing of biliary stricture.